Blue Ocean Strategy: Marketing Strategy to achieve Competitive Advantage - Ismail Razak (Jurnal Sosial Sains dan Komunikasi, 2023)
Blue Ocean Strategy emphasizes the creation of new markets without direct competition, which has the potential to increase product differentiation and attract new customers. This research aims to investigate the concept of Blue Ocean Strategy as an innovative approach in marketing strategy to achieve competitive advantage. This research uses a qualitative approach with descriptive methods. The research results show that the application of the Blue Ocean Strategy as a marketing strategy to achieve competitive advantage has a significant positive impact. Companies that successfully implement this strategy are able to create new markets or change the dynamics of existing markets, bring unique product or service innovations, and provide differentiating customer experiences. Additionally, companies that successfully integrate cost reduction or efficiency improvements in their strategy can offer products or services at more competitive prices, strengthening competitiveness in the Blue Ocean. Strategic communication and gradual implementation play a key role in ensuring understanding and support from internal and external companies. Continuous evaluation and adjustment provides an opportunity for companies to remain responsive to market changes, maintain a competitive advantage, and ensure continued growth in their newly discovered markets.